Cyber Crime and The Use of Internet Banking in The Community of Denpasar City - Desak Made Sukarnasih; Sriary Bhegawati, Desak Ayu (Ilomata International Journal of Management, 2023)
The three objectives of this study were to determine: 1) the effects of internet banking on cybercrime in Denpasar City; 2) the effects of consumer protection for users of internet banking facilities on cybercrime in Denpasar; and 3) the effects of both the use of internet banking and consumer protection for users of internet banking facilities on cybercrime in Denpasar. This is a quantifiable research with population comprising the residents of Denpasar . The information was collected through a survey with 150 respondents using an unintentional selection technique. To evaluate the data collection, the traditional premise test, the multiple linear regression analysis, the coefficient of determination test (R2), and the hypothesis test (F-test and t-test) were all implemented. The outcome demonstrates: 1) The use of internet banking positively impacts cybercrime in Denpasar. 2) Consumer protection for users of internet banking facilities positively impacts cybercrime in Denpasar. 3) The use of internet banking positively impacts both consumer protection for users of internet banking facilities and cybercrime in Denpasar.